Changes in clinical features of coeliac disease in adults in Edinburgh and the Lothians 1960-79. Issue 6359 (8th January 1983) - Logan, R F; Tucker, G; Rifkind, E A; Heading, R C; Ferguson, A
Abstract : From 1960 to 1979 there was a threefold increase in the number of cases of coeliac disease diagnosed annually in adults in Edinburgh and the Lothians. Women accounted for 80% of the increase and their mean age at diagnosis was significantly reduced. The ratio of female to male new cases changed from 1.25 in the '60s to 2.5 in the '70s. In the period 1975-9 56 of 102 adults with coeliac disease presented with no gastrointestinal symptoms, including 30 cases diagnosed as a result of minor biochemical or haematological abnormalities, such as red-cell macrocytosis without anaemia. Over the same period, only 13 presented with a typical malabsorption syndrome compared to 24 of 38 (63%) in the years 1960-4. During 1975-9 58 new cases had no anaemia, compared with eight (21%) in the earlier period. Hypoproteinaemia (concentration less than 60 g/l) and hypocalcaemia of less than 2.00 mmol/l (8 mg/100 ml) were also less common. Though a real increase in the incidence of coeliac disease cannot be discounted, these changes are more likely to be the result of greater awareness of the disease and a lowered threshold for investigation.